First Tobacco Product Tried: Associations with Smoking Status and Demographics among College Students - Sutfin, Erin L. (Addict Behav, 2015)
INTRODUCTION: As the tobacco market expands, so too have the opportunities for youth to be introduced to nicotine. The goal of this study was to identify product choice for initial tobacco trial, correlates associated with product choice, and the relationship between first product and current cigarette smoking among college students. METHODS: A cross-sectional web survey of 3,146 first-year students at 11 universities in North Carolina and Virginia was conducted in fall 2010. RESULTS: Weighted prevalence of ever use of tobacco was 48.6%. Cigarettes were the most common first product (37.9%), followed by cigars (29.3%), hookahs (24.6%), smokeless tobacco (6.1%), and bidis/kreteks (2.2%). Two thirds (65%) of current smokers initiated with cigarettes, but 16.4% started with cigars, 11.1% with hookahs, 5.7% with smokeless, and 1.7% with bidis/kreteks. Females were more likely to report their first product was cigarettes and hookahs, while males were more likely to start with cigars and smokeless tobacco. Compared to those whose first product trial occurred after the age of 18, younger age of initiation (17 years or younger) was associated with cigarettes and smokeless as first products, while older age of initiation (18 or older) was associated with starting with hookahs and cigars. Dual or poly tobacco use was more common among those who initiated with hookahs and smokeless tobacco. CONCLUSIONS: While over a third of students used cigarettes first, two thirds started with a non-cigarette product. Just about a third of current cigarette smokers initiated with a non-cigarette product, suggesting that those non-cigarette products may have facilitated escalation to cigarettes.